Peningkatan Kemampuan Operasi Hitung Pengurangan Siswa Kelas 1 MI dengan Media Abacus di Indonesia - Utami, Sri; Huda, Nurul (Journal of Elementary Education Research, 2024)
AbstractThis study aims to improve the ability of subtraction calculation operation of first grade students of Madrasah Ibtidaiyah (MI) Tarbiyatul Athfal Gembong Pati using abacus media in learning. This research is a Classroom Action Research. The research subjects were first grade students of MI Tarbiyatul Athfal which amounted to 29 students by involving the principal as a collaborator and researchers as accompanying teachers and observers. This research was conducted for 2 cycles with data collection techniques using observation, documentation, and tests. Data analysis techniques use averages and percentages. The research ended if it had reached the predetermined criteria. The results showed that the implementation of the learning process in cycle I reached 96%, while in cycle II it reached 100%. The average score in the pre-cycle stage reached 57.6, in cycle I reached 68.3, and in cycle II reached 77.6. At the pre-cycle stage, students who reached the KKM score amounted to 6 people (20.7%). At the cycle I stage, students who reached the KKM amounted to 18 people (62.1%). At the cycle II stage, students who reached the KKM amounted to 25 people (86.2%) so that it had reached the research completeness criteria of 85%. Abacus media has an impact in improving students' subtraction calculation skills. Therefore, the ability of subtraction calculation operation with abacus media in MI students has increased.